CAPITAL STRUCTURE DETERMINANTS AND THE SPEED OF ADJUSTMENT TOWARDS CAPITAL STRUCTURE TARGET: EVIDENCE FROM PROPERTY COMPANIES IN INDONESIA - Ayu C Wibowo Putri, Novialita
This study provides the empirical evidence of the capital structure determinants and the speed of adjustment to reach the target of firms. Initially, the topic of property development in developing countries has become very interesting to study because of the rapid growth in emerging countries. Especially in Indonesia, with recent regulations and president’s focus on the growth of the country, this industry has been targeted by investors to jump in. This study uses financial reports from each firm during the period between 2009 and 2016. In accordance with the industry-specified variables, this study examines the importance of property industry-specific determinants of capital structure. In this study, we tried to validate our model and theory on a sample of property companies in Indonesia with two models which are not mutually exclusive but rather complementary one another. We use static model to validate the determinants of capital structure, then use dynamic model to estimate the speed of adjustment towards capital structure target for property companies in Indonesia. The result shows that property companies in Indonesia have several property industry-specific determinants. Target capital structure does exist for property companies in Indonesia with a considered slow speed of adjustment towards capital structure target.